AN INVERSE-PHOTOEMISSION STUDY OF EMPTY ELECTRONIC STATES IN TIO2 - Taverner, A; Hollamby, P; Aldridge, P; Egdell, R; Mackrodt, W (1993)
Empty electronic states in rutile (TiO2) have been studied by inverse photoemission spectroscopy at (110) and (001) surfaces. The spectra reveal a 2 eV splitting of the empty Ti 3d bands into π* and σ* components, with an overall Ti 3d bandwidth of order 6 eV. These values are in good agreement with periodic ab initio Hartree-Fock calculations. © 1993.